Immunoglobulin Replacement Therapy in Secondary Hypogammaglobulinemia - Compagno, Nicolò; Malipiero, Giacomo; Cinetto, Francesco; Agostini, Carlo (Frontiers in Immunology, 2014)
Immunoglobulin (Ig) replacement therapy dramatically changed the clinical course of primary hypogammaglobulinemias, significantly reducing the incidence of infectious events. Over the last 2 decades its use has been extended to secondary antibody deficiencies, particularly those related to hematological disorders as lymphoproliferative diseases (LPDs) and multiple myeloma. In these malignancies, hypogammaglobulinemia can be an intrinsic aspect of the disease or follow chemo-immunotherapy regimens, including anti-CD20 treatment. Other than in LPDs the broadening use of immunotherapy (e.g. rituximab) and immune suppressive therapy (steroids, sulfasalazine, mycophenolate mophetil) has extended the occurrence of iatrogenic hypogammaglobulinemia. In particular, in both autoimmune diseases and solid organ transplantation Ig replacement therapy has been shown to reduce the rate of infectious events. Here, we review the existing literature about Ig replacement therapy in secondary hypogammaglobulinemia, with special regard for subcutaneous administration route, a safe, effective and well-tolerated treatment approach, currently well established in primary immunodeficiencies and secondary hypogammaglobulinemias.